Determination of linagliptin and empagliflozin by UPLC and HPTLC techniques aided by lean six sigma approach. (20th March 2021) - El‐Desouky, Ebrahim A.; Abdel‐Raoof, Ahmed M.; Abdel‐Fattah, Ashraf; Abdel‐Zaher, Ahmed; Osman, Ayman O. E.; Abdel‐Monem, Ahmed H.; Morshedy, Samir
Abstract: Two chromatographic techniques were developed and validated for simultaneous determination of the newly co‐formulated antidiabetic combination linagliptin and empagliflozin in their pure form and film‐coated tables. The first technique was UPLC; the separation and resolution of both analytes were achieved using a Zorbax eclipse plus C18 column applying an isocratic elution based on phosphate buffer pH 4–acetonitrile (65:35, v/v) as a running mobile phase at flow rate 1.5 ml/min and the effluent was monitored at 220 nm. Augmentation of Lean Six Sigma with UPLC and HPTLC methods had a major impact on the development of robust specifications to ensure that the quality at six sigma level has a high level of statistical confidence and target performance. On the chromatogram, empagliflozin and linagliptin appeared at retention times of 1.417 and 2.453 min, respectively. The second technique was HPTLC; both analytes were fairly well resolved and separated using a developing mobile phase composed of ethyl acetate–chloroform–acetonitrile (55:25:20 by volume). The values of retention factor (RF ) were 0.29 and 0.53 for linagliptin and empagliflozin, respectively. All variables were investigated to adjust the whole conditions.